How highway landscape visual qualities are being studied: a systematic literature review - Gao, Hangyu; Abu Bakar, Shamsul; Maulan, Suhardi; Mohd Yusof, Mohd Johari; Mundher, Riyadh; Chen, Benxue (Multidisciplinary Digital Publishing Institute, 2024)
Highways play a vital role in the road transport system, connecting regions and cities in many parts of the world. It may sometimes offer scenic views or a visually appealing environment based on the availability of unique compositions of natural and man-made elements within the highway vicinity. The highway’s landscapes could significantly impact the journey experience; thus, it is essential to emphasize the need to preserve a visually appealing, safe, and enjoyable highway environment. Although many studies have been conducted regarding the highway visual environment, currently, there is a lack of comprehensive understanding of perception variables that could affect viewers’ preference for highway landscapes. Therefore, this study aims to understand the background of the highway landscape and identify the perception variables and their effect on the preference for highway landscapes. This study conducted a systematic review by searching for keywords in three databases: Web of Science, Scopus, and Google Scholar. The review included 37 research articles published between 1993 and 2023 that met the criteria. An additional nine relevant papers were included through a ‘snowballing’ approach to supplement the research and results. The results of the study focused on multiple perspectives of highway landscape views, viewers’ perspectives and the diversity of highway landscape purposes, viewers’ preferences for highway landscapes, the approach to preferences, and related key variables. This background knowledge deepens the understanding of visual preferences for highway landscapes and helps refine the selection of perceptual variables, establishing an essential reference criterion for professionals.